Dose-dependent activity of albendazole against benzimidazole-resistant nematodes in sheep: relationship between pharmacokinetics and efficacy - Moreno Torrejon, Laura (2004)
The relationship between the pharmacokinetic behaviour and the anthelmintic efficacy of albendazole (ABZ) against benzimidazole (BZD)-resistant nematodes was studied in sheep. A micronized ABZ suspension was orally administered at two different dose levels to sheep naturally infected with BZD-resistant gastrointestinal (GI) nematodes. The experimental animals were allocated into the following groups (n=8): (a) untreated control; (b) orally treated with ABZ at 3.8 mg/kg b.w.; and (c) orally treated with ABZ at 7.5 mg/kg b.w. Plasma samples were obtained serially over 72 h post-treatment from both treated groups and analysed by HPLC to measure the concentrations of ABZ and its sulphoxide (ABZSO) and sulphone (ABZSO2) metabolites. Faecal egg counts were performed prior to treatment and at the necropsy day. All experimental animals were sacrificed 10 days after treatment to perform GI worm counts. While ABZ parent drug was not recovered in the bloodstream, ABZSO and ABZSO2 were the molecules found in plasma. ABZSO was the metabolite measured at the highest concentrations in the bloodstream for up to 36 (treatment at 3.8 mg/kg) or 60 h (treatment at 7.5 mg/kg) post-administration. There was a proportional relationship between the administered ABZ dose and the measured plasma concentrations of both ABZ metabolites. Over a 100% increment on the plasma AUC values for the anthelmintically active ABZSO metabolite was observed at the 7.5 mg/kg compared to the 3.8 mg/kg treatment. The low efficacy patterns (<24%) observed against the GI nematodes investigated indicate a high level of resistance to ABZ given at 3.8 mg/kg an efficacious therapeutic dose rate recommended in some countries. However, the higher and prolonged plasma drug concentration measured after the 7.5 mg/kg treatment resulted in an improved efficacy pattern (estimated by both faecal egg and adult worm counts) against most of the GI nematodes studied compared to that obtained at the lower dose rate. A direct relationship between drug pharmacokinetic behaviour and anthelmintic efficacy against BZD-resistant nematodes in sheep was shown in the current work, although individual variation precluded the observation of statistically significant differences in worm counts.